Αποτελεσματικότητα της μουσικοθεραπείας σε παιδιά με αναπτυξιακές διαταραχές - Κωνσταντινίδου, Μαρία (Τμήμα Νοσηλευτικής, Σχολή Επιστημών Υγείας, Τεχνολογικό Πανεπιστήμιο Κύπρου, 2011)
Background: Music therapy is a therapeutic form that uses music as a therapeutic stimulus to achieve non-musical therapeutic goals and can be effective in facilitating growth in many areas of functioning of children. Aim: This paper aims of this critical literature review was to investigate the effectiveness of music therapy in children with developmental disorders. Sample and method: We applied a critical review of research literature. The sample was found from the databases EMBASE, MEDLINE, CINAHL and PUBMED. As key words using the following conditions: usefulness of music therapy, effectiveness of music therapy, special education, art therapies, special education and music therapy, individual educational. Ultimately included 6 research studies that met the criteria for admission set. Results: In children with delayed development of speech, the music therapy has improved presentation. The phonological ability and speech understanding of children increased, and the cognitive structures, the mode of action and level of intelligence, the difference between developmental age and biological age of the children decreased significantly and developmental age of children converged with their biological age. Also, children develop non-verbal communication and social skills and communication skills. Conclusion: Music therapy has had positive effects and outcomes, with substantial indications supporting the value of music to promote social, emotional and motor development in children with developmental disorders and had thetikin effect on the development of several skills in children with developmental disorders.
Keywords: Music therapy; Child Developmental Disorders--therapy